Software architecture superstream. (O'Reilly Media, Inc., 2022)
Just as developers use design patterns in software development, architects use architecture patterns to define the characteristics and shape of the architecture of a system. Using the right architecture pattern is critical because once in place the architecture is very hard to change. Using the wrong architecture pattern (or no pattern at all) can be a very costly mistake, resulting in an architecture that may not work. But how do you decide which pattern to use? Join us for four hours of sessions on some of the most popular and useful architectural patterns and how to implement them at your organization. About the Software Architecture Superstream Series: This five-part series of half-day online events focuses on the hottest topics in software architecture, giving you the insights to keep pace with what's next while still accommodating legacy needs. Both seasoned software architects and those looking to break into the field will learn new skills and the latest information on the tools and technologies they need to succeed. What you'll learn and how you can apply it Understand the similarities and differences between architecture patterns and design patterns Learn how to use patterns in microservices-style architectures Get a glimpse of the future of event-driven architectures and patterns This live event is for you because... You're a senior-level developer who wants to make the move to architect. You're a practicing software architect who wants to hone your skills and learn new software architecture techniques and practices. You want to better understand how to use patterns to improve your software architecture. Recommended follow-up: Listen to Microservices Patterns (audiobook) or read the book Read Software Architecture Patterns (report) Watch Software Architecture Fundamentals (video) Read Building Micro-Frontends (early release book) Read Fundamentals of Software Architecture (book) Watch Introduction to Cloud Native Architecture Patterns (video).